2006
DOI: 10.1016/j.febslet.2005.12.086
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐specific angiogenesis inhibitor 2 regulates VEGF through GABP that acts as a transcriptional repressor

Abstract: Previously, we reported that decreased brain-specific angiogenesis inhibitor 2 (BAI2) induced increased VEGF expression. The regulatory mechanisms for this process are not understood. Here we show that GA-binding protein gamma (GABPc) associates with the cytoplasmic domain of BAI2, and GABPa/c or GABPa/b works as a transcriptional repressor of VEGF in SHSY5Y cells. Transcriptional activity of wild-type VEGF promoter was significantly increased in anti-sense BAI2-transfected cells, but not that of VEGF promoter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…Decreased VEGF and Robo4 expression after GABPa/ b gene transfer in conjunctival epithelial cells GABPa/b was reported to act both as a transcriptional repressor of VEGF expression in SH-SY5Y and CV-1 cells 21 and as an activator with SP1 of the human Robo4 promoter in primary endothelial cells. 23 We chose human Chang conjunctival epithelial cells to test the expression of the GABPa/b gene in the conjunctiva and cornea by transiently transfecting these cells with increasing doses of lipoplexes carrying a plasmid encoding for the human GABPa and GABPb (GABPa/b) genes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Decreased VEGF and Robo4 expression after GABPa/ b gene transfer in conjunctival epithelial cells GABPa/b was reported to act both as a transcriptional repressor of VEGF expression in SH-SY5Y and CV-1 cells 21 and as an activator with SP1 of the human Robo4 promoter in primary endothelial cells. 23 We chose human Chang conjunctival epithelial cells to test the expression of the GABPa/b gene in the conjunctiva and cornea by transiently transfecting these cells with increasing doses of lipoplexes carrying a plasmid encoding for the human GABPa and GABPb (GABPa/b) genes.…”
Section: Resultsmentioning
confidence: 99%
“…16 In the present study, we examined the possibility that subconjunctival delivery of the GABP transcription factor to neovascularized cornea could affect the expression patterns of VEGF and Robo4, which were reported to be transcriptionally regulated by GABP and to be critical regulatory proteins in pathologic angiogenesis. 21,23,25,26 Using this approach, we observed for the first time that GABP could delay new vessel formation in a mouse neovascularized cornea for up to 2 weeks after subconjunctival injection of lipoplexes carrying the GABPa/b plasmid DNA adjacent to the corneal neovascular area. We found that gene delivery of the GABPa/b plasmid DNA reduced VEGF and Robo4 expression in conjunctival epithelial cells and in mouse neovascularized cornea, and that GABPa/b-injected cornea had significantly less neovascular area and fewer vessels than did the emptyvector-treated or experimental control groups.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The antiangiogenic activity of BAI1 is thought to be mediated by a fragment of its N-terminal extracellular sequence, a fragment known as vasculostatin (17,23,24). BAI2 and BAI3 expression are not p53-inducible, but both proteins also act as inhibitors of angiogenesis (11,14,15,25). Moreover, BAI1 functions as a surface receptor for phosphatidylserine that is exposed on the surface of apoptotic cells, suggesting that BAI1 is an engulfment receptor that can initiate phagocytosis (26).…”
mentioning
confidence: 99%